La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Alanis Obomsawin: Lifework - Hill, Richard William; Peleg, Hila; Haus der Kulturen der Welt (Prestel Publishing, 2022)
"One of today's most important documentary filmmakers, Alanis Obomsawin has dedicated her life's work to shining a light on the injustices experienced by Canada's Indigenous people. This retrospective monograph features an extensive interview with Obomsawin and includes stills and reflections on her entire career including her most recent series devoted to the rights of Indigenous children. Never shying away from controversy, Obomsawin's films have played a critical role in exposing ongoing systemic bias towards Indigenous populations-from fishing rights and education to health care and treaty violations. Obomsawin is also a graphic artist, and she incorporates her often dream-inspired etchings and prints into many of her films. This volume includes illuminating essays exploring Obomsawin's practice and mission as well as personal commentary from collaborators, archival materials, and photographs from the filmmaker's personal life and professional exploits. As Obomsawin closes in on her ninth decade of life-and fifth decade behind the camera-this beautifully illustrated record of her astounding body of work and tireless efforts on behalf of Indigenous peoples and culture is an inspiring celebration of the power of film to dramatically change the course of history"-- Provided by publisher.

“Before I made fims, I was singing” - Obomsawin, Alanis; Gagnon, Monika Kin (Alanis Obomsawin: Lifework, 2022)

Étude patrimoniale sur le katajjaniq - Gadoua, Marie-Pierre (Publications Nunavik, 2021)
Ce livre présente une résumé exhaustif de l’étude effectuée sur le katajjaniq, suite à la désignation de cette pratique à titre de premier élément du patrimoine immatériel québécois.

Dream visions: The Art of Alanis Obomsawin - Obomsawin, Alanis (Perceval Press, 2021)